Accounting Students’ Experience Using Quizizz for Vocabulary Learning at SMK Muhammadiyah 3 Banjarmasin - Putri, Yuniarty; Rahman, Faisal; Azmi, Aulia; Azhimia, Faida (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
Vocational high school students struggle to master English vocabulary due to limited study time, low motivation, and a lack of engaging learning resources. Vocabulary mastery is crucial because it helps students develop their speaking, listening, reading, and writing skills. This is especially true for accounting students who must use English for work purposes. Gamification and interactivity are implemented in technology-based programs, such as Quizizz, to enhance learning effectiveness and enjoyment. In this study, 10th-grade accounting students at SMK Muhammadiyah 3 Banjarmasin were asked about their experiences using Quizizz as a vocabulary learning tool. Thirty students selected from a total sample were used in a quantitative descriptive study. A 20-item survey covering five indicators—motivation, engagement, perceived ease of use, feedback, and vocabulary learning outcomes —was used to collect data. Descriptive statistics were used to examine the data. Feedback was shown to have the highest mean score (3.72), followed by engagement (3.68), perceived ease of use (3.63), motivation (3.57), and vocabulary learning outcome (3.49). These results indicate that students consider Quizizz a useful tool for vocabulary acquisition. The platform’s interactive and game-based elements encourage students' participation, increase motivation, and provide rapid feedback to aid vocabulary learning. In conclusion, Quizizz creates a positive learning experience, increases engagement, and provides useful feedback for vocabulary acquisition.